ESTRATÉGIA EMPRESARIAL: PRESENÇA DA RESPONSABILIDADE SOCIAL NA EDUCAÇÃO CORPORATIVA UM ESTUDO DE CASO NO SETOR DE ENERGIA - Sa, Ricardo Luiz Paes de (2008)
Companies need to have a well-prepared staff loaded with abilities and specific competences in contemporary society. Corporative universities are responsible for providing, within the companies, the immediate competences needed to be dynamic and present appropriated educational solutions in the short, middle and long run. The objective of this dissertation is to discuss the evaluation of the long-term courses thrown in a corporative university as well as to propose an evaluation method of the performance of the courses, including measurements of the return of the investment in doing it so. The research proposal was to analyze the efficiency of the applied training after one year of the end of the course, co-relating the academic contents with in-loco practices. The applied methodology was a qualitative one, using focus groups (with employees that have attended these courses) and interviews (with the managers of those employees), creating inputs to implement improvement for the next class to be planned. Results show that the courses fulfill their strategic role providing technical knowledge. However, it still lacks to feedback the employees with the socio environmental responsibilities, which, in fact, is one of the strategic pillars of the company.